2022
DOI: 10.1007/s11357-022-00561-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients

Abstract: Background Persistent viral RNA shedding of SARS-CoV-2 following COVID-19 has increasingly been recognized, with limited understanding of its implications on outcomes in hospitalized COVID-19 patients. Methods We retrospectively assessed for persistent viral shedding across Northwestern Medicine Healthcare (NMHC) patients between March and August 2020. We assessed for predictors of persistent viral shedding, in-hospital delirium, and six-month mortality using binary log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…COVID-19 patients may be particularly prone to agitated encephalopathy. Studies have found that 30% to 51.8% of critically ill COVID-19 patients had at least one episode of hyperactive delirium, which is substantially higher than the pre-pandemic incidence of 12.7% in critically ill patients [50,54,55]. The reason behind this high rate of agitation in COVID-19 patients is unclear; this could be related to the greater severity of COVID-19 lung injury and higher levels of ventilatory support, the frequent use of prone positioning, a relatively higher incidence of young individuals needing critical care during early COVID-19 surges, crisis staffing with providers less experienced in effective sedation management, decreased family visitation, or perhaps biological mechanisms unique to SARS-CoV-2 infection [50,[55][56][57][58].…”
Section: Epidemiology and Presentationmentioning
confidence: 94%
See 3 more Smart Citations
“…COVID-19 patients may be particularly prone to agitated encephalopathy. Studies have found that 30% to 51.8% of critically ill COVID-19 patients had at least one episode of hyperactive delirium, which is substantially higher than the pre-pandemic incidence of 12.7% in critically ill patients [50,54,55]. The reason behind this high rate of agitation in COVID-19 patients is unclear; this could be related to the greater severity of COVID-19 lung injury and higher levels of ventilatory support, the frequent use of prone positioning, a relatively higher incidence of young individuals needing critical care during early COVID-19 surges, crisis staffing with providers less experienced in effective sedation management, decreased family visitation, or perhaps biological mechanisms unique to SARS-CoV-2 infection [50,[55][56][57][58].…”
Section: Epidemiology and Presentationmentioning
confidence: 94%
“…The mechanism of persistent cognitive dysfunction in Neuro-COVID is likely a complex interplay of fatigue, sleep disruption, aberrant immune response, and potential persistent infection [156,157]. Lack of oxygen does not seem to be responsible as impaired cognition can occur in patients with mild COVID-19 who were never hypoxic.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Batra et al (60) demonstrated that persistent viral shedding in patients was associated with in-hospital delirium episodes and a higher mortality rate. Notably, in the study by Dias et al (61), delirium was not found to have a higher prevalence in the COVID-19 group compared with the non-COVID-19, while it appeared to manifest in a more severe form in the COVID-19 group.…”
Section: Introductionmentioning
confidence: 99%